Characteristics of China’s digital economy network and its impact on carbon emissions - Wang, Huiping; Liu, Peiling (Frontiers in Ecology and Evolution, 2023)
Accurately grasping the correlation of digital economy between cities is an important foundation for scientifically formulating regional coordinated development strategies, and also an important entry point for achieving the goal of "carbon peaking and carbon neutrality". Using data for 248 cities in China from 2011 to 2019, social network analysis is conducted to examine the overall and individual characteristics of the digital economy network (DEN), and the effects of the DEN's central characteristics on carbon emissions are empirically assessed. Research conclusions include the following: first, the digital economy of these 248 cities in China exhibits a clear spatial network structure, but the overall network structure is relatively loose, with fewer connections between cities, representative of the initial form of the network. Second, the Yangtze River Delta Urban Agglomeration, as represented by Wuxi, Suzhou, and Nanjing, occupies a core position in the network. Only 35 cities fulfil an intermediary role, influencing the connections between other cities. More than 40% of cities are strongly connected with nondirect partners. Third, the improvement in the central position of the DEN significantly increases carbon emissions, but the direction and intensity exhibit high heterogeneity with differences in resource endowment and population size. Fourth, the central characteristics of the DEN indirectly promote carbon emissions by increasing energy consumption. These research findings complement the existing research on the relationship between DEN and carbon emissions, providing valuable policy implications for governments and scholars.